Investigating the Role of Current Strength in tDCS Modulation of Working Memory Performance in Healthy Controls - Teo, Florence; Hoy, Kate E.; Daskalakis, Zafiris J.; Fitzgerald, Paul B. (Frontiers in Psychiatry, 2011)
Transcranial direct current stimulation (tDCS) is brain stimulation technique that has the potential to improve working memory (WM) deficits in many clinical disorders. The aim of this study was to investigate the role of current strength on the ability of anodal tDCS to improve WM, and secondly to investigate the time course of effects. Twelve healthy participants underwent three stimulation sessions consisting of 20 minutes of either 1mA anodal tDCS, 2mA anodal tDCS or sham tDCS to the left dorsolateral prefrontal cortex (DLPFC) localised via F3, all whilst completing a WM task. Intrastimulation and post stimulation WM performances were measured using the n-back and Sternberg tasks respectively. Results revealed no significant improvements in participants’ accuracy but a significant interaction was found with respect to current strength and time for accurate reaction time. The finding provides partial support for the hypothesis, in that it appears current strength may affect aspects of WM performance. However, more research is needed, and a higher difficulty level of WM tasks is one of the suggestions discussed for future research.